A Phase II study of SGN‐30 (anti‐CD30 mAb) in Hodgkin lymphoma or systemic anaplastic large cell lymphoma - Forero‐Torres, Andres; Leonard, John P.; Younes, Anas; Rosenblatt, Joseph D.; Brice, Pauline; Bartlett, Nancy L.; Bosly, Andre; Pinter‐Brown, Lauren; Kennedy, Dana; Sievers, Eric L.; Gopal, Ajay K. (British journal of haematology, 2009)
Summary SGN‐30, a chimeric anti‐CD30 monoclonal antibody, has demonstrated potent preclinical antitumour activity in both Hodgkin lymphoma (HL) and anaplastic large cell lymphoma (ALCL). We conducted an open‐label, Phase II study to determine the safety and objective response rate of SGN‐30 in 79 patients with refractory/recurrent HL (n = 38) or systemic ALCL (n = 41). Each course of SGN‐30 comprised 6 weekly intravenous infusions, followed by a 2‐week treatment‐free period. Patients had received a median of 3 (range 1–5) prior regimens of chemotherapy or systemic therapy. The initial 40 patients received 6 mg/kg weekly; the latter 39 patients received 12 mg/kg weekly. In the ALCL group, two patients achieved a complete response and five additional patients achieved a partial response, with response durations ranging from 27 to 1460+ d. No objective responses were observed in the HL group; however, 11 patients (29%) had stable disease (duration 62–242 days). Although adverse events were common, most were mild or moderate, and no specific pattern of adverse events was observed in either disease group. These results demonstrate that weekly administration of SGN‐30 is safe, with modest clinical activity in patients with ALCL.